Chinese Vaccine Providers' Perspectives on the HPV Vaccine. (October 2020) - Ji, Mengdi; Huang, Zhuoying; Ren, Jia; Sun, Xiaodong; Wagner, Abram L.
China approved a human papillomavirus (HPV) vaccine in 2018. Recommendations from health care providers can positively impact vaccine receipt. This study characterized vaccine providers' attitudes toward the HPV vaccine and contrasted attitudes by the providers' demographic characteristics. In total, 120 vaccine providers in Shanghai, China, completed a questionnaire. Associations between essential characteristics of the HPV vaccine and providers' urbanicity and working length were explored using the Kruskal-Wallis test. Doctors with ≤5 years' work experience were more likely to think it important to emphasize that HPV is a sexually transmitted disease compared to doctors with longer work experiences ( P = .0231). More suburban than urban providers thought that China should include the HPV vaccine into the publicly funded Expanded Program on Immunization ( P = .0315). Differences in attitudes toward HPV could lead to variation in how providers talk to parents and adolescents about the HPV vaccine, with disparities in vaccine uptake as a result.